A family of mechanically adaptive supramolecular graphene oxide/poly(ethylenimine) hydrogels from aqueous assembly. Issue 6 (18th January 2017) - Wang, Chao; Duan, Yipin; Zacharia, Nicole S.; Vogt, Bryan D.
Abstract : Cooperative aqueous assembly of graphene oxide and poly(ethylenimine) generates a nanocomposite whose modulus irreversibly responds to applied compression and increases up to 3 orders of magnitude in a tunable manner. Abstract : Composite hydrogels containing graphene oxide (GO) offer advantageous mechanical properties, but tuning these properties generally requires the synthesis of new hydrogels or if the hydrogel is thermally responsive, utilization of a chemistry determined temperature window. Here, we demonstrate a simple route to generate a family of GO-based hydrogels from aqueous solution based assembly of GO with polycationic poly(ethylenimine), PEI, without any secondary chemical crosslinking. Tuning the ratio of GO : PEI during the assembly produces a family of hydrogels that responds to mechanical compression by irreversibly altering their equilibrium water content and mechanical properties in a controllable manner. Despite the lack of chemical crosslinks, the hydrogels are stable when stored in an excess of water or NaCl solutions (up to 1 M) and exhibit a tunable swelling ratio (mass hydrogel : mass solid) between 44 and 162 based on both composition and compression history. Consequently, the storage modulus from shear rheology can be increased by more than 3 orders of magnitude from this irreversible mechanical compression of the hydrogel. This stiffening of the hydrogels in response to mechanical stimuli enables the prior compression loading of the hydrogel to be determined. We demonstrate that this strategy is generalizable to other anionic 2D materials such as clay (cloisite). This family of mechanically adaptive hydrogels enables facile fabrication and tuning of physical properties that could be advantageous for sensing, energy dissipation, and other applications.